Pengembangan E-Module Fisika Aktif Berpendekatan Information Search - Gloria Adolfina Kairmo; Tursina Ratu; Hermansyah Hermansyah; Fahmi Yahya; Syarif Fitriyanto (Fakultas Keguruan dan Ilmu Pendidikan Universitas Samawa, 2021)
The learning process so far has only been sourced from textbooks, resulting in a low understanding of physics concepts owned by students. In addition, the learning model that is less varied makes students not actively involved in learning. The active physics E-Module with an Information Search approach provides new treasures in the learning process that increases the activeness and independence of students in learning. The purpose of this study was designed to determine (1) the feasibility of the product in the form of physics E-Module teaching materials that are integrated with Information Search type active learning, (2) to find out the students' responses to the active physics E-Module teaching materials with an Information Search approach that was developed. This research is a Research and Development (R&D) research with a 4D model but is limited to 3 stages, namely the Define stage, Design (Design); and Development (Development) on a limited trial. The instrument used in this research is a questionnaire on the feasibility of the material and media as well as a practitioner response questionnaire with a Likert scale. The results showed that the active physics E-Module with an Information Search approach was feasible to use in physics learning based on expert judgment with an acquisition percentage of 84.4% included in the